A review of neck injury and protection in vehicle accidents. Issue 2 (11th November 2019) - Li, Fan; Liu, Niansong; Li, Honggeng; Zhang, Biao; Tian, Shiwei; Tan, Minggang; Sandoz, Baptiste
Abstract: Neck injury is one of the most common types of injury in vehicle accidents. The mechanisms of neck injury remain controversial due to the complex structure of the cervical spine and various impact conditions. The aim of the present study is to provide a summary of recent research on neck injury mechanisms, neck injury criteria and neck injury prevention measures. The main types of neck injury resulting from vehicle accidents, including whiplash injury, cervical bone fractures and spinal cord injury, are introduced. Neck injury mechanisms are summarized according to load directions, test or simulation methods, and thresholds by means of impact intensity, load intensity and stress/strain conditions. Neck injury criteria are introduced, including NIC, Nij, Nkm and LNL. Passive and active technologies for neck injury prevention are described and the challenge of neck injury prevention for future intelligent vehicles is discussed.